The impact of health service quality on patient satisfaction - an exploratory study at the Digestive and Liver Teaching Hospital in Baghdad - Amirat Shakar Waliun Al-Bayati (Iraqi Journal for Administrative Sciences, 2025)
Given the importance of hospitals to create a generation of good health and reduce the problems experienced by, it was necessary to raise the efficiency of its services, and the standard of living, in terms of design, organization and availability of modern instruments and equipment in order to achieve patient satisfaction, which is the fundamental basis for the survival of organizations, health and growth. Interested in research on how to measure patient satisfaction, health services provided in a hospital in the digestive tract, liver, education, commensurate with their needs and their health conditions, to improve the quality of service provided to them, and to identify the strengths & weaknesses to achieve the desired differentiation from other hospitals operating in the same jurisdiction. The research objectives were: the how to measure patient satisfaction with the services provided to them and the factors influencing them through the use of Likert scale quintet. The research found significant results are to improve the performance of the health service from the perspective of patients, as provided by a hospital of the digestive system, liver, education from the comfort and tranquility, and good health services, the speed of the reception and treatment of patients, according to their health needs.